2017
DOI: 10.1002/etc.3925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spray drift of glyphosate on nontarget terrestrial plants—A critical review

Abstract: Glyphosate is a widely used broad-spectrum postemergent herbicide used for weed control in both agricultural and nonagricultural settings. Spray drift of glyphosate can pose a risk to nontarget terrestrial plants and plant communities outside the intended area of application, but the lack of a well-established predicted-no-effect drift rate makes properly assessing such risk difficult. For this reason, a literature review and meta-analysis was carried out with the aim to determine the level of drift that is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…In particular, as stated by the Regulation (EC) 1107(EC) /2009(EC) (2009, it is desirable to reduce pesticide input and have a correct use of chemicals when and where they are needed. In the case of Roundup, the latter aspect is not entirely negligible, given that very often, in common agricultural practices, it is over-sprayed without precautions for avoiding drift spray (low-drift and low-pressure injectors) and without respecting buffer zones (Cederlund 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, as stated by the Regulation (EC) 1107(EC) /2009(EC) (2009, it is desirable to reduce pesticide input and have a correct use of chemicals when and where they are needed. In the case of Roundup, the latter aspect is not entirely negligible, given that very often, in common agricultural practices, it is over-sprayed without precautions for avoiding drift spray (low-drift and low-pressure injectors) and without respecting buffer zones (Cederlund 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Even with aerial spraying of glyphosate, plant injury is usually minimal at distances of >20 m downwind from sprayed fields (Marrs et al 1993;Reddy et al 2010). For mature plants of many species, there is minimal damage at distances of less than 20 m. Wild plant species are generally less sensitive to glyphosate than domesticated plant species (Cederland 2017). An analysis by Cederland (2017) found that drift of 5 g ae h −1 of glyphosate would result in minor adverse effects of drift on 95% of plant species and that drift levels of 1 to 2 g ae h −1 of glyphosate would essentially cause no harm to vascular plants.…”
Section: Real and Potential Effects On Non-target Vegetation And Micrmentioning
confidence: 99%
“…Moreover, ecotoxicological and resistance-related consequences of the extended use of glyphosate (Schütte et al, 2017) or of the use of GT GM crops (Pandolfo et al, 2018) have been emphasized, along with effects non-target terrestrial plants as well (Cederlund, 2017). As for emerging plant resistance against glyphosate, glyphosate itself and glyphosate-based herbicides have been shown to affect the disease resistance and health of plants by undermining their innate physiological defenses in mechanisms related to the mode of action of glyphosate, even in crops engineered for glyphosate-tolerance, and by interferences with the local microbial ecology in the rhizosphere (Martinez et al, 2018).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%